2019
DOI: 10.1123/jab.2018-0297
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Dependent Changes in Soleus Length–Tension Behavior Augment Ankle Joint Quasi-Stiffness

Abstract: The triceps surae muscle-tendon units are important in governing walking performance, acting to regulate mechanical behavior of the ankle through interaction between active muscle and passive elastic structures. Ankle joint quasi-stiffness (the slope of the relation between ankle moment and ankle rotation, k A), is a useful aggregate measure of this mechanical behavior. However, the role of muscle activation and length-tension behavior in augmenting k A remains unclear. Here, 10 subjects completed eccentric is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…b Average GAS fascicle length (adapted from Browne and Franz[29]) and peak SOL activation reported as a percent of maximum voluntary isometric contraction (i.e., %MVC) (adapted from Franz and Kram[31]) during walking in young (gray) and older (black) adults. c SOL muscle stiffness, given by the relationship between SOL muscle force and SOL muscle length, in young adults during isokinetic eccentric contractions of the triceps surae muscles as a function of muscle activation (α -indicated with the large arrow from α = 0 to 75%) prescribed via biofeedback, adapted from Clark and Franz[34]. d Model-predicted effects of peak Achilles tendon strain (ε o ) on GAS and SOL mass-normalized metabolic energy consumption.…”
mentioning
confidence: 99%
“…b Average GAS fascicle length (adapted from Browne and Franz[29]) and peak SOL activation reported as a percent of maximum voluntary isometric contraction (i.e., %MVC) (adapted from Franz and Kram[31]) during walking in young (gray) and older (black) adults. c SOL muscle stiffness, given by the relationship between SOL muscle force and SOL muscle length, in young adults during isokinetic eccentric contractions of the triceps surae muscles as a function of muscle activation (α -indicated with the large arrow from α = 0 to 75%) prescribed via biofeedback, adapted from Clark and Franz[34]. d Model-predicted effects of peak Achilles tendon strain (ε o ) on GAS and SOL mass-normalized metabolic energy consumption.…”
mentioning
confidence: 99%
“…This is likely due to the small size of our perturbations compared to earlier studies. All previous estimates of human triceps surae muscle stiffness used perturbations at least twice as large as those we applied (20° or larger) [12, 38]. Previously, Hauraix et al [12] reported a triceps surae muscle stiffness value of 218 N/mm at 40% MVC, while Clark et al [38] reported a muscle stiffness of 118 N/mm at 25% MVC.…”
Section: Discussionmentioning
confidence: 93%
“…All previous estimates of human triceps surae muscle stiffness used perturbations at least twice as large as those we applied (20° or larger) [12, 38]. Previously, Hauraix et al [12] reported a triceps surae muscle stiffness value of 218 N/mm at 40% MVC, while Clark et al [38] reported a muscle stiffness of 118 N/mm at 25% MVC. For comparison, we estimate muscle stiffness to be 261 N/mm at 25% MVC for an average participant in our study.…”
Section: Discussionmentioning
confidence: 93%
“…We estimated the rate of force development for the gluteus maximus and vastus lateralis muscles based on EMG data, which is appropriate since linear envelope EMG closely resembles muscle force [34,41]. While this approach accounts for the muscle activation-dependent active components muscle force, it does not account for force produced by passive properties of the muscles and tendons [42]. Since force plate data only describe net forces, we estimated muscle force from EMG to provide a muscle-based metric of rate of force development despite the limitations.…”
Section: Discussionmentioning
confidence: 99%